Complex phyto-vitamin drugs for acute respiratory infections - V.M. Delyagin (LCC «Medicine-Inform», 2019)
V.M. Delyagin Dmitry Rogachev State National Research Center of Pediatric Hematology, Oncology and Immunology, Moscow, Russian Federation Acute respiratory infections (ARI) of the upper respiratory tract (in general, viral) are the most common infectious disorders both in children and adults characterized by typical tropism and seasonality. High rate of ARI in children is accounted for by more contacts of children after leaving family circle and as well as immaturity of innate immunity. ARI of the upper respiratory tract account for 67% to 84% of respiratory disorders (depending on the age group). Despite the fact that ARI are mostly self-limiting, sometimes they affect child's health and the parents greatly. A variety of pathogens, variable clinical manifestations, self-limitation, a growing number of resistant strains, unnecessary prescription of antibiotics for viral infections, and the risk of adverse reactions when treating viral infections with broad-spectrum antibiotics justify complementary and alternative treatment. Modern phytotherapy and vitamins relieve symptoms and provide immunomodulatory ef fects. KidZ syrup with Althaea and plantain improving dry and productive cough as well coughing at night is recommended. Vitamin C, Althaea, plantain, chamomile, and thyme provide analgesic, anti-inflammatory, sedative, and mild immunomodulatory effects. Keywords: children, respiratory diseases, viral infections, vitamins, herbal remedies. For citation: Delyagin V.M. Complex phyto-vitamin drugs for acute respiratory infections. Russian Journal of Woman and Child Health. 2019;2(4):347-350.